Analisis Motivasi dan Kerjasama Tim terhadap Produktivitas PT Pradana Indah Sejahtera - Ilma Sofyana Padang; David Humala Sitorus (Universitas Batanghari, 2022)
This study aims to analyze the effect of motivation on productivity, teamwork on productivity, and the effect of motivation and teamwork simultaneously on productivity at PT Pradana Indah Sejahtera. The population of this study were 253 employees. The technique of determining the number of samples taken as respondents in this study is to use Solvin so that the number of samples is 155 employees. Questionnaire as the main data collection tool. Data analysis in this study used multiple linear regression analysis method. The results of the analysis show that the motivation variable has a positive and significant effect on productivity, the teamwork variable has a positive and significant effect on productivity, and the motivation and teamwork variables have a positive and significant effect on productivity. This research has theoretical and managerial implications.